Family Experiences in Treating Children with HIV/AIDS Through ARV Therapy in Jayapura City - Suryati Romauli; Sri Wahyuni (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
HIV / AIDS is a chronic disease, can not be cured completely and the incidence rate is always there in every year, so it can have broad impact on all aspects of life especially physical, psychological, social, and spiritual. Thus can affect the quality of life of patients themselves. HIV/AIDS infected more than 90% of children in 2020, acquired from their mothers. In accordance, special protection from families is crucial. Antiretroviral is the best therapy in PLWHA children’s treatment, and family support is needed to succeed. The objective of this study is to explore in detail family experiences in nurturing HIV/AIDS children with ARV therapy in Jayapura City. Methods: This research is qualitative research with a phenomenology approach. The selection of participants was obtained by purposive sampling, and 8 participants were selected to be interviewed using voice recorder and file notes. Data were analyzed using nine stages of Colaizzi. Results: There are five themes, namely: the initial obstacles faced by the family of ODHA children; Family efforts to care for children living with HIV/AIDS;  Constraints in child care;  Form of health care workers; Fulfilling physical, psychological, and laboratory needs. Conclusion: Participants lacking in knowledge regarding  HIV/AIDS. Consequently, it became the major obstacle faced by families of ODHA children, this affecting delayed child's HIV status, but in terms of child care, there is a lot of support for children